BUCCAL FILM: A NOVEL APPROACH FOR ORAL MUCOSAL DRUG DELIVERY SYSTEM - HAJU, SHIFA; YADAV, SHEELA; BAIG, REESHA; SAWANT, GAURANG (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Buccal drug delivery especially refers to the delivery of drugs through the buccal mucosal membrane lining of the oral cavity. For geriatric and pediatric patients who undergo difficulties in swallowing conventional oral solid dosage forms, the buccal film is a better alternative. The buccal film is appropriate for the drugs which experience high first-pass metabolism and is used for enhancing bioavailability with reducing dosing frequency to mouth plasma peak levels, which thus limit side-effects and make it cost-effective. It enhances the efficacy of API in the oral cavity after the contact with less saliva as contrasted to tablets, without chewing and no need for water for administration. This review briefly describes the advantages and limitations of buccal film, an anatomical structure of oral mucosa, highlighting the mechanisms of drug permeation, formulation technologies, methodology in evaluating buccal film, and recent advances of the buccal film as a tool for drug delivery for various treatments.